Mimetic orthosis for lower limbs to be applied on rehabilitation for hemiplegic persons - Luna., P. S.; Cardiel., E.; Muñoz., R.; Urrutia., R.; Villanueva., D.; Hernández., P. R. (Revista Mexicana de Ingenieria Biomedica, 2008)
A rehabilitation tool based on an innovative mimetic active orthosis for hemiplegics is presented. It follows concepts of neuronal learning from afferent information from movements, similar to those lost after brain damage. An artificial gait pattern is applied on knee and hip articulations of a functionally modified limb by using an exoskeleton powered by pneumatic muscles.